Organizational Culture as a Mediating Variable in the Relationship of Changing Management Strategies and Employee Acceptance of Technological Change at the University of Basra - Al-frijawy , Jawad; Abbas, Yasir (The Gulf Economist, 2025)
This study explores the relationship between branding and competitive advantage in the Iraqi retail sector, focusing on the key dimensions of cost, quality, flexibility, and delivery, and addressing the ambiguity surrounding the extent to which brand elements such as identity, personality, association, and adequacy contribute to building organisational superiority. Employing a descriptive-analytical methodology supported by a field survey distributed to a sample of retail stores in Baghdad, the study analyzed the data using the statistical program (SPSS) to measure the strength of relationships between variables and test the proposed hypotheses. The findings reveal a strong and statistically significant correlation between branding and competitive advantage, demonstrating that branding has a clear impact on the dimensions of cost, quality, and flexibility, while its influence on delivery is relatively weaker. The results also indicate challenges related to weak cost-control practices and limited ability to anticipate future customer needs, contrasted with strong performance in delivery accuracy and responsiveness to customers’ individual requirements. The importance of this study lies in its contribution to enriching Iraqi and Arab literature on competitive advantage while providing a practical framework that organizations can adopt to develop more effective marketing strategies, strengthen their market position, and achieve sustainable growth and survival in an increasingly dynamic business environment